2018
DOI: 10.2528/pierc18061805
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Modified Circular Slot Antenna for Wlan and Wimax Applications

Abstract: In this article, design and analysis of a modified circular slot antenna is discussed. The proposed antenna design is attractive because of two important reasons: (i) modified circular slot creates dual operating bands; (ii) stable radiation characteristics over the operating frequency bands are observed. The complete analysis of proposed radiator has been done on Ansys HFSS simulation software. For verifying the simulated outcomes, a prototype of antenna structure is fabricated and tested. Measured results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Although the antenna in [20] had a simple design, it did not cover all the required frequencies and had lower gain compared with our design. The antenna in [21] covers only two bands and printed on Taconic RF-35 which makes its construction complicated. [22] And [23] proposed a larger antenna size compared to our antenna design with varying gain levels.…”
Section: Fabrication Resultsmentioning
confidence: 99%
“…Although the antenna in [20] had a simple design, it did not cover all the required frequencies and had lower gain compared with our design. The antenna in [21] covers only two bands and printed on Taconic RF-35 which makes its construction complicated. [22] And [23] proposed a larger antenna size compared to our antenna design with varying gain levels.…”
Section: Fabrication Resultsmentioning
confidence: 99%
“…A T-shaped slot with a rectangular patch was introduced to achieve dual-band operation in the 2.4 GHz and 5.8 GHz frequency bands for wireless local area networks (WLANs) [27]. Zhu et al [28] proposed a T-slot microstrip patch antenna with a fork-shaped feeding structure to achieve tri-band operation for Wi-Fi, Bluetooth, and 5G systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Slot structures are commonly used to achieve bandwidth enhancement in multiband printed antennas. Traditional slot fractal shapes and other structures have been effectively used to design antennas with and multiband for a variety of wireless applications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Sze et al [7] suggested a low profile dual-band Annular Ring Slot Antenna (ARSA) for the use in 2.4/5 GHz (WLANs).…”
Section: Introductionmentioning
confidence: 99%